Analysis of Language Learning Strategies in Learning English as a Foreign Language - Mendrofa, Elvienna Sally Juwita; Zebua, Ardi Syah Putra; Waruwu, Yaredi (CV. Ulil Albab Corp, 2025)
English is the first foreign language in the world that is used as an international language and several countries make this language their daily language. Likewise in Indonesia, English is a language that must be studied in schools. There are several strategies that can be used by school teachers to teach English, including: the TPR method (Total Physical Response Method), story telling, pictures and songs so that it makes it easier for them to like learning English.